The Antimicrobial Defense of the Pacific Oyster, Crassostrea gigas. How Diversity may Compensate for Scarcity in the Regulation of Resident/Pathogenic Microflora - Schmitt, Paulina; Rosa, Rafael D.; Duperthuy, Marylise; de Lorgeril, Julien; Bachère, Evelyne; Destoumieux-Garzon, Delphine (Frontiers in Microbiology, 2012)
Healthy oysters are inhabited by abundant microbial communities that vary with environmental conditions and coexist with immunocompetent cells in the circulatory system. In Crassostrea gigas oysters, the antimicrobial response, which is believed to control pathogens and commensals, relies on potent oxygen-dependent reactions and on antimicrobial peptides/proteins (AMPs) produced at low concentrations by epithelial cells and/or circulating hemocytes. In non-diseased oysters, hemocytes express basal levels of defensins (Cg-Defs) and proline-rich peptides (Cg-Prps). When the bacterial load dramatically increases in oyster tissues, both AMP families are driven to sites of infection by major hemocyte movements, together with bactericidal permeability/increasing proteins (Cg-BPIs) and given forms of big-defensins (Cg-BigDef), whose expression in hemocytes is induced by infection. Co-localization of AMPs at sites of infection could be determinant in limiting invasion as synergies take place between peptide families, a phenomenon which is potentiated by the considerable diversity of AMP sequences. Besides, diversity occurs at the level of oyster AMP mechanisms of action, which range from membrane lysis for Cg-BPI to inhibition of metabolic pathways for Cg-Defs. The combination of such different mechanisms of action may account for the synergistic activities observed and compensate for the low peptide concentrations in C. gigas cells and tissues. To overcome the oyster antimicrobial response, oyster pathogens have developed subtle mechanisms of resistance and evasion. Thus, some Vibrio strains pathogenic for oysters are equipped with AMP-sensing systems that trigger resistance. More generally, the known oyster pathogenic vibrios have evolved strategies to evade intracellular killing through phagocytosis and the associated oxidative burst.